Structural studies of oligometric enzymes - Bloomer, A; Bloomer, A.C. (1972)
﻿ The functions of biological macromolecules are discussed in relation to their structure as linear polymers adopting specific conformations. If such molecules can be crystallised, their three dimensional structure can be determined at atomic resolution by the methods of X-ray crystallography whose applicability to the analysis of protein structures is considered. This is followed by an account of their application in the study of a glycolytic enzyme, triose phosphate isomerase (TIM), leading up to the calculation of an electron density map at 2.5andnbsp;andAring; resolution. The characteristics of crystals of chicken TIM are described and a detailed account is given of the measurement of X-ray diffracted intensities, the determination and refinement of the positions of heavy atom binding in isomorphous derivatives of TIM, and their subsequent use for calculating the phases of the protein structure factors. The search which was conducted for possible heavy atom derivatives produced several which have two sulphydryl sites in common. The problems resulting from these common sites and the systematic errors they can cause in the phase determination are examined in relation to the suitability of different methods of refinement in this situation. The electron density map of TIM at 6andnbsp;andAring; Resolution is described and a preliminary discussion of the 2.5andnbsp;andAring; map is given.